Quality Assurance, Metrics, and Improving Standards in Rectal Cancer Surgery in the United States - Xu, Zhaomin; Fleming, Fergal J. (Frontiers in Oncology, 2020)
Rectal cancer surgery has seen significant improvement in recent years. This has been possible in part due to focus on surgeon education and training, specific surgical quality metrics, and longitudinal tracking of data through the use of registries. In countries that have implemented such efforts, data has shown significant improvement in outcomes. However, there continues to be significant variation in rectal cancer outcomes and practices worldwide. Just within the United States, county level mortality rates from rectal cancer range from 8-15 per 100,000 to 38-59 per 100,000. In order to continue to improve rectal cancer patient outcomes, there needs to be evidence based guidelines and standards centered around the framework of structure, process, and outcomes. In addition, there must be a feedback system by which programs can continually assess their performance. Obtaining evidence for specific standards and measures can be challenging and requires analyzing available data and literature, some of which may be conflicting. This article evaluates the evolution of metrics and standards used for quality improvement in rectal cancer and ongoing efforts to further improve patient outcomes.